METHODS OF DEVELOPING MEDIA TECHNOLOGIES IN PEDAGOGICAL HIGHER EDUCATION INSTITUTIONS - Feruza Madrahimova (Scholar Express Journal, 2022)
The growing national and international processes of information privatization. Media criticism is seen as a real ally of media education. Foreign and some domestic theorists of media education as an integral part of activities aimed at education and personal development with the help and material of mass media in order to form a culture of communication with the media, creative, communication skills, critical thinking, the ability to independently analyze, interpret and evaluate media texts
Keywords: Media criticism; human information culture; media messages; articles